A coupled finite element-least squares point interpolation/boundary element method for structure-acoustic system with stochastic perturbation method. (October 2020) - Zhang, Na; Yao, Lingyun; Jiang, Guoqi
Abstract: Finite element-least squares point interpolation method (FE-LSPIM) developed recently shows some excellent features to improve the calculation accuracy of mechanical problems. In this paper, a coupled finite element-least squares point interpolation method/ boundary element method (FE-LSPIM/BEM) is proposed to analyze plate-like structural-acoustic coupled system. Here, the FE-LSPIM is used to model the structure domain, while the acoustic domain is modeled by BEM. The hybrid method not only inherits advantages of element compatibility of the finite element method (FEM) and the quadratic polynomial completeness of LSPIM, but also improves the calculation accuracy of the structural domain. Moreover, stochastic perturbation method is introduced to process uncertainty parameters of the FE-LSPIM/BEM, so the stochastic perturbation FE-LSPIM/BEM model has been proposed, then several uncertain parameters that have been randomly processed were used to increase the analytical reliability in structural-acoustic coupled system. At last, numerical examples are taken to verify the feasibility of the proposed SP-FE-LSPIM/BEM as compared to Monte Carlo method (MCM) and stochastic perturbation finite element/boundary element method (SP-FEM/BEM). The results show that FE-LSPIM/BEM has higher accuracy in analysis of uncertain structural-acoustic coupling system as compared to the FEM/BEM.